A High-Quality Genome Resource for the Oak Wilt Pathogen Bretziella fagacearum - Karandeep Chahal; Mohit Mahey; Carmen Medina-Mora; Steven Ahrendt; Robert Riley; Anna Lipzen; Juying Yan; Emily Savage; Maxim Koriabine; Vivian Ng; Igor V. Grigoriev; Thomas C. Harrington; et al. (PhytoFrontiers)
Bretziella fagacearum is a destructive vascular wilt fungal pathogen affecting oaks in the United States and Canada. The epidemiology of oak wilt varies across different geographical locations, indicating the need to investigate the population dynamics of B. fagacearum to discern potential differences in its genotypes using genomic tools. A good-quality genome of B. fagacearum is crucial as a reference for population genetics studies. Here, we report a high-quality genome of B. fagacearum isolate C519. The genome assembly consists of nine scaffolds, corresponding to the nine chromosomes, totaling 27,072,536 bp with a GC content of 47.29%. It is predicted to encode 7,554 proteins, which are annotated using RNA sequencing data from the same isolate. The circular mitochondrial genome consists of a chromosome of 174,403 bp with a GC content of 28.59% and contains 54 open reading frames, including 14 core genes, 28 tRNAs, 4 rRNAs, and 8 hypothetical proteins. The reference genome can enhance the understanding of molecular epidemiology and biology of B. fagacearum, aiding in identifying genetic variations and pathogen–host interactions and developing diagnostic tools and disease management strategies. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2025.